Personality profile of athletes practising endurance disciplines - Piepiora, Paweł; Migasiewicz, Juliusz; Napieraj, Dominika (Journal of Education, Health and Sport, 2019)
This paper concerns issues in the field of sport psychology. The purpose of the study was to determine the personality profile of athletes practising endurance disciplines – an individual one and a team one. The five-factor NEO-FFI personality inventory was used. The study involved senior-age men (N=60) engaged in the competitive practice of long-distance running (n=30) and football (n=30). It was demonstrated that long-distance runners are characterised by an average level of neuroticism, extraversion, openness to experience and agreeableness and a high level of conscientiousness, while football players are different from the former, to a statistically significant degree, with regard to neuroticism and extraversion (higher in football players) and conscientiousness (higher in runners). The personality profile of long-distance runners differs from that of football players. The biggest discrepancies were revealed on the conscientiousness scale. A significant impact of the sport discipline practised on the personality profile of athletes was confirmed.